PENGEMBANGAN MODUL PENGAJUAN CUTI DAN DANA - Oktivasari, Prihatin; Irawati, Dwi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
Service employees is an activity that is essential for any company. The larger the company would have more and more employees. Therefore the company is required to perform the service employees in a fast, accurate and on target. Companies that have employees many of course have large amounts of data. Such data require good organization to generate maximum performance. Office Automation System with the use of the Internet (web-based) can support the provision of information and processing data quickly and accurately. This technology is a solution for the employee to perform services specifically leave application and submission of funding without having to come directly to the company. With the leave application module that employees can perform leave application anytime and anywhere. While the funding submission module can control submitted for the employees often make companies lose. Back end system built using CodeIgniter PHP framework and frontend using Bootstrap CSS framework for the system to be accessed in a variety of platforms while using MySQL database. System testing is done using the Black-box testing methods, ie functional testing system to ensure that the system created in line with expectations and the companyâs business processes. From the results of tests performed, it can be concluded that the system has been running in accordance with the business processes and the companyâs expectations. Use of office automation systems can handle the existing problems, especially in the leave application modules and submission of funding.